Ethical issues that confront nurses in private hospitals in the Western Cape Metropolitan area - Ethelwynn L. Stellenberg; Alta J. Dorse (AOSIS, 2014)
Background: Nurses are faced daily with a variety of ethical issues which could be as a result of budget cuts, target setting, the shortage of nurses and expertise. Objectives: The objectives of the study were to identify ethical issues related to patient care, to describe ethical issues related to patient diversity, rights and human dignity. To describe ethical issues related to caring in nursing and to the workplace environment. Method: A quantitative explorative descriptive research design was applied. A stratified sample of (n = 142/5%) was drawn from all nurses and caregivers (N = 2990) working in a selected group of eight private hospitals. Self-administered questionnaires were used to collect the data. Statistical tests were applied to determine statistical relationships between variables. Results: Results included (95%) of respondents provided safe and committed care to their patients, (99%) loved to care for their patients and (93%) believed in the Nurses' Pledge of Service. Fifty percent (50%) of the respondents indicated verbal abuse from patients and only (59%) experienced openness and transparency in the work environment. Analysis further identified that the caregivers did not respect the noble tradition of the profession and experienced the most verbal abuse. Conclusion: This study has identified ethical issues which may give rise to conflict within the workplace environment if not adequately addressed by management. The study further showed that the use of caregivers not regulated in nursing practice may pose as a threat to the safety of the patient.